Influence of enclosure condition and visitor numbers on behaviour of captive Malayan tapir - Arumugam, Kalai Arasi (2018)
The population of Malayan tapirs (Tapirus indicus) in the wild is experiencing a radical decline mainly due to habitat destruction throughout their regions. Often during in search for a new habitat, food or mating partner, tapirs are victimised to traffic accidents when the roads are cutting through their habitats. In Peninsular Malaysia, a total of 68 tapirs death were recorded within five years since year 2012. Therefore, as an initiative measure to sustain the population, ex-situ conservation was established. However, the ability of captive management to maintain and breed endangered species has been proved challenging. While many other wild animals under captivity showed changes in their natural behaviours that resulted in stress, breeding difficulties, poor health, and repetitive stereotypic behaviours, information on Malayan tapir is still lacking. Hence, instantaneous sampling over 20 minutes period with an interval of 30 seconds was used to investigate the effects of enclosure type and size, weather (temperature and humidity) and the number of visitors on a range of behaviours to determine their role as potential stressors in male and female captive Malayan tapirs. Analysing the data using generalised linear mixed-effects models and multiple regression models, it was found that enclosure type had a significant effect on feeding behaviour where tapirs in semi natural enclosures fed more frequently than tapirs in artificial enclosure, mirroring natural feeding activity. Enclosure condition was also found to increase the investigative behaviour and reduced the time spent on resting in artificial enclosures. High visitor numbers overall lowered activity of tapirs, while low humidity caused tapirs to suffer from dryness, and thus resulted in more frequent snout licking as an indicative of thermal stress. In addition, increased number of visitors had reduced the sexual interaction such as, initiation, antagonistic and vocalisation in both male and female Malayan tapirs. Overall from this study, it is concluded that unsuitable enclosure conditions of extreme dryness and number of visitors are prone to be potential stressors that lower the activity pattern that possibly alter the natural behaviours of Malayan tapir. Therefore, further evaluation on exhibit design and management practices are encouraged to identify variables that could increase the reproductive success and physical well-being of captive Malayan tapirs.